Analytical study of a manuscript, Tafsir Ayat Mushkilah min Al-Kitab "Interpreting of equivocal Quranic signs (verses)” - Brahimi, Tahar; Guechi, Afaf (The International tax journal, 2025)
This study introduces a significant manuscript in the field of Qur’anic studies, titled “Equivocal Qur’anic Verses” by Shaykh Al-Mukhtar Al-Kunti the Elder. The research is structured to highlight the manuscript's content, versions, and scholarly value. It begins with an introduction to the author, Shaykh Al-Mukhtar Al-Kunti, outlining his background and contributions to Islamic scholarship. The study then explores the purpose of the manuscript, provides an analysis of its various extant copies, and confirms its attribution to Al-Mukhtar Al-Kunti. Additionally, it examines the specific issues addressed within the manuscript, offering a detailed examination of Shaykh Al-Mukhtar’s approach to elucidating equivocal (Almushkil) verses of the Qur’an. The study aims to provide a comprehensive understanding of the manuscript’s context, significance, and the author’s methodology in clarifying ambiguous Qur’anic verses.